2020
DOI: 10.1111/ijfs.14786
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different nut oils on the structures and properties of gel‐like emulsions induced by ultrasound using soy protein as an emulsifier

Abstract: Stable gel‐like emulsions were prepared by high intensity ultrasound (HIU). Nut oils influenced the physicochemical properties of gel‐like emulsions. Oil/water surface tension influenced the particle size. Sunflower oil gel‐like emulsion had the highest storage and freeze‐thaw stability. Walnut and pine nut oil samples showed larger particle size and lower viscoelastic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 57 publications
(75 reference statements)
1
15
0
Order By: Relevance
“…The viscosity of the U emulsion was significantly higher than that of the C emulsion at low shear rate; this result may be related to the particle size of the emulsion. Smaller droplet sizes lead to a closer spacing, thereby enhancing hydrodynamic interactions and improving viscosity [22] . Moreover, the increase in emulsion viscosity can decelerate the movement and collision frequency of droplets and ultimately effectively resist flocculation and coalescence between droplets [21] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The viscosity of the U emulsion was significantly higher than that of the C emulsion at low shear rate; this result may be related to the particle size of the emulsion. Smaller droplet sizes lead to a closer spacing, thereby enhancing hydrodynamic interactions and improving viscosity [22] . Moreover, the increase in emulsion viscosity can decelerate the movement and collision frequency of droplets and ultimately effectively resist flocculation and coalescence between droplets [21] .…”
Section: Resultsmentioning
confidence: 99%
“…Both the increase in WHC and the decrease in EMC reflected that the 3D network structure of surimi gel tended to be dense and orderly. As a result, more water molecules were trapped and retained in the gel network to avoid leakage [22] . In addition, the fat globules dispersed in the emulsion interacted with protein; the resulting interfacial protein film was also conducive to restricting the flow of fat and water in the mixed gel network [5] , [20] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before HIU application, the oleogels formed with pine nut oil and walnut oil showed higher intensities than the peanut oil sample. According to our previous research (Table S 1) [57] , the concentrations of C 18:0 in all the nut oils were low (<4%), but the amount of C 16:0 in peanut oil was higher than pine nut and walnut oils. Previous studies showed that the crystalline network of oleogels is mainly formed by the interaction of long-chain fatty acids with n-alkanes [26] .…”
Section: Resultsmentioning
confidence: 65%
“…Ultrasound technology is increasingly employed as a homogenization technology in the production of EFGs with many studies demonstrating it to be an advantageous tool in developing stable functional EFGs (Geng et al, 2021;Hu et al, 2021;Huerta et al, 2020;Paradiso et al, 2015).…”
Section: Introductionmentioning
confidence: 99%